Using sodium glycodeoxycholate to develop a temporary infant-like gut barrier model, in vitro - Bietto, Francesca; Arranz, Elena; Miralles, Beatriz; Gómez-Marín, Cristina; Rath, Eva; Lucey, Alice J.; Giblin, Linda (Frontiers in Nutrition, 2025)
IntroductionIn newborns, the intestinal barrier is permeable but not inflamed. Understanding this unique state is essential for developing models relevant to infant gut physiology.MethodsThis study aimed to develop an in vitro model of the infant gut barrier treating Caco-2/HT29-MTX with 0.5, 0.8, and 1 mM sodium glycodeoxycholate (GDC).ResultsOur research demonstrates that GDC decreases Caco-2/HT29-MTX Trans-Epithelial Electrical Resistance (TEER) and increases paracellular permeability, without inflammation or cytotoxicity. Notably, the treatment with 0.8 mM GDC increased lactulose transport rate by 1.63-fold. The treatment also reduced the key tight junction protein, occludin, at the cell membrane, and increased acidic mucins and extracellular alkaline phosphatase activity. Additionally, GDC decreased cAMP, suggesting its mechanism of action was via activation of a G-protein coupled receptor. Of particular importance to nutrition studies, the GDC effect was reversible with TEER recovery within 4 h. Applying digested infant formula to 0.8 mM GDC-treated Caco-2/HT29-MTX monolayers resulted in a higher concentration of amino acids in the basolateral compartment compared to control monolayers.DiscussionThese findings suggest that GDC can modulate gut barrier properties in a controled, reversible manner, offering a valuable model for studying nutrient absorption and gut physiology in early life.